Influence of Packaging, Price, Promotion and Perceived Value on Purchase Decision at Snack Business 88 Solok - Amril, Dody; Heryanto, (Technium Social Sciences Journal, 2020)
This study is aimed to find the influence of packaging, price, promotions and perceived value on purchase decision at Snack Business 88 Solok. The method used in this study is quantitative research with a descriptive approach. The population in this study was resellers who shop at Snack Business 88 Solok City. The sample used was 72 resellers by using accidental sampling. The data analysis is multiple linear regressionstechnique.The results of the study show that: (1) Packaginghas a positive and significant effect on purchase decision at Snack Business 88 Solok City, (2) Price has a negative and significant effect on purchase decision at Snack Business 88 Solok City, (3) Promotion has a positive and significant effect on purchase decision at Snack Business 88 Solok City, (4) Perceived value has a positive and significant effect on purchase decision at Snack Business 88 Solok City, (5) Packaging, price, promotion and perceived value have a significant effect on purchase decision at Snack Business 88 Solok City.